Increasing the contribution of strong panel zones to the plastic deformation capacity of post-Northridge welded connections - Hedayat, Amir A.; Celikag, Murude (World Scientific And Engineering Acad And Soc, 2008)
This study aimed to obtain a balance condition for post-Northridge connections with strong panel zones (PZ) by introducing a series of circular holes in the PZ. Hence, a pre-tested post-Northridge connection was modeled using FEA. Analytical results showed that a hole radius of 50 mm and a balance ratio of 0.81 appeared to be the optimum configuration for increasing the PZ plastic rotation. This increase would, however, only increase the total plastic rotation capacity of the connection by 10 percent. Further, a function was proposed to determine the PZ shear yielding resistance in the presence of a circular hole in PZ.
WSEAS International Conference on Engineering Mechanics, Structures, and Engineering Geology -- JUL 22-24, 2008 -- Heraklion, GREECE
Keywords: Post-Northridge connections; panel zone; ductility; inelastic shear deformation